Evaluation of MUREX SUDS Toxo test. - Moyer, N P (1987)
The SUDS Toxo test (MUREX Corp., Norcross, Ga.) was compared with the indirect hemagglutination test (IHA) and the indirect fluorescent-antibody test (IFA) by examining 404 serum specimens, including 64 (15.8%) specimens with IFA titers of greater than or equal to 1:2. When SUDS was compared with IHA, sensitivity (96.4%), specificity (97.9%), and negative predictive value (99.4%) indicated that there were similar reactivities between the two tests. When an IFA titer of greater than or equal to 1:16 was considered significant and IHA and SUDS were compared with IFA, IHA was slightly less sensitive but had a higher positive predictive value than did SUDS; however, there was no statistical difference between the tests. When SUDS was compared with IFA, in which a titer of greater than or equal to 1:16 was considered significant, the high negative predictive value (100%), excellent sensitivity (100%) and specificity (98.3%), and ease of performance made SUDS an attractive alternative to IHA for screening single serum specimens for toxoplasmosis.